Gangrenous aplasia cutis congenita of the scalp. A marker of severe hemorrhage and epileptic attacks. - Buquicchio, R. (European Journal of Pediatric Dermatology, 2009)
Aplasia cutis congenita (ACC) is a rare disorder characterized by absence of the skin and, at times, of the underlying tissues at birth. In most cases the lesions affecting the scalp, particularly the vertex area, are isolated, small in size and not responsible for therapeutical problems. Exceptionally, extensive lesions are covered at birth by a blackish eschar. In the latter case, the healing is slower and possibly complicated by severe hemorrhage. Here are reported two newborn infants with gangrenous ACC of the scalp, complicated by multiple hemorrhages and seizure in the first month of life.